1998
DOI: 10.1007/s005860050102
|View full text |Cite
|
Sign up to set email alerts
|

Fatal pulmonary fat embolism after dorsal spinal fusion

Abstract: IntroductionFatal clinical fat embolism is a rare complication in elective orthopaedic surgery. Microscopic fat embolism caused by bone marrow fat drops have been described in over 90% of intramedullary procedures in long bones during total hip and knee implantations, and in trauma patients, especially with femoral shaft fractures. The incidence of clinically noticeable fat embolism syndrome in those patients is 0.5-23% [6,7], with a mortality of 10-20% [5]. Usually clinical symptoms appear within 3 days, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Additionally, bone marrow in children contains proportionately more hematopoietic tissue than fat, as compared with adults. Fatal fat embolism after spinal fusion surgery is also a very rare occurrence, with only three reported cases to our knowledge (3)(4)(5), only one of which involved a pediatric patient (4).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, bone marrow in children contains proportionately more hematopoietic tissue than fat, as compared with adults. Fatal fat embolism after spinal fusion surgery is also a very rare occurrence, with only three reported cases to our knowledge (3)(4)(5), only one of which involved a pediatric patient (4).…”
Section: Discussionmentioning
confidence: 90%
“…Spinal cord ischemia leading to neurologic abnormalities as a result of stretching of the anterior spinal arteries, induced hypotension during surgery, or compression from spinal implants may also be seen. Pulmonary fat embolism is a very rare complication, and to our knowledge only three cases have been reported previously (3)(4)(5). We report the case of a fatal pulmonary fat embolism following spinal fusion surgery.…”
mentioning
confidence: 78%
“…Twentyfour studies performed surgery in the prone position (Table 1), and 7 studies investigated complications following lumbar spine surgery in the knee-chest position (Table 2). 1,2,[5][6][7][9][10][11]13,15,18,19,[21][22][23][24][25][26]28,29,[32][33][34]36,37,39,40,42,[46][47][48] Complications related to the knee-elbow, lateral decubitus, and supine positions were each reported by a single study (Table 3). 14,30,31 prone-position studies Vision loss was the most commonly reported complication, with 11 case reports describing postoperative-onset vision loss.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…4,12 Use of pillows and careful positioning of the abdomen and extremities diminish these pressure points as well. 1,2,5,29 The risk and consequences of developing pressure sores is important. This review highlights the need for future studies comparing the relative risk of pressure sores following the use of various tables and frames.…”
mentioning
confidence: 99%
“…Postulations for this variation could be due to the difference in marrow composition as the proportion of haematopoietic tissue to fat in a child’s bone marrow is more than that found in adults 1. Thus, there are only case reports of this condition in paediatric patients which mainly involve spinal fusion or screw augmentations 13. The following is the first report of FES in a paediatric patient after a minor procedure with removal of femoral implant.…”
Section: Introductionmentioning
confidence: 99%